The genius of Judy : how Judy Blume rewrote childhood for all of us - Bergstein, Rachelle (One Signal Publishers, Atria, 2024)
Offers an intimate and expansive look at Judy Blume's life, work and cultural impact, focusing on her most iconic--and controversial--young adult novels, from Are You There God? It's Me, Margaret to Blubber.